“MULTIMODAL ARTERIOGRAPHY IN OTORHINOLARYNGOLOGY: ROLE IN PULSATILE TINNITUS AND VASCULAR PATHOLOGY OF THE EAR.” - MACIAS OROSCO, TATIANA KARINA (2026)
Pulsatile tinnitus represents 5-10% of tinnitus cases and is characterized by the perception of sound synchronous with the cardiac pulse. Its etiology is frequently related to vascular pathology of the temporal bone, including arteriovenous malformations, vascular anomalies, and hypervascularized tumoral lesions. Pulsatile tinnitus constitutes a relatively infrequent clinical manifestation, but of high diagnostic relevance in otorhinolaryngology, since in a significant percentage of cases it reflects the presence of underlying vascular pathology of the ear, skull base, or cerebral circulation. Unlike subjective tinnitus, pulsatile tinnitus is usually associated with potentially treatable entities such as arteriovenous malformations, dural fistulas, vascular anatomical variants, or paraganglioma tumors, which requires a precise and systematic diagnostic approach. In this context, it is essential to critically review the role of multimodal arteriography in the diagnosis and management of vascular pathology of the ear and, in particular, in the evaluation of pulsatile tinnitus. An updated synthesis of the literature will allow for the identification of the strengths and limitations of each technique, the establishment of indication criteria, and the definition of the added value of invasive arteriography compared to non-invasive modalities. This work aims to carry out a systematic and critical literature review on the role of multimodal arteriography in otorhinolaryngology, emphasizing its application in the differential diagnosis of pulsatile tinnitus and in the management of vascular pathology of the ear, including glomus tumors, arteriovenous malformations, dural fistulas, and clinically relevant anatomical variants.